Paper Money Value Change: Comparative Banking Fiqhiyyah Study - Hamzah Abdu Karim (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2013)
This article considered one of the significant issues in Islamicfinancial fiqh because it bears a close relation to financial commitment. Many fiqh treatments from a Sharia perspective were found in Islamic ancient fiqh. This issue was apparent in Islamic banks investment especially in murâbahah. The study concludes that it is a must who owes amount of money and its value changes to high or low to pay the value of money then,and not the actual amount. Furthermore, it shows that the treatment of fluctuations in money value comes by linking its value with some indicators, including stable currency and the linkage to gold or silverDOI: 10.15408/aiq.v5i1.2561